A simple non-graphic method for pedigree description and analysis. Issue 1 (February 1977) - Schaap, T; Cohen, M M
Abstract : The graphic representation of family data for the computation of the coefficients of inbreeding [F] and relationship [r] can be replaced by an algebraic method. The organization of family data is facilitated by a data form which can be easily, thoroughly, and correctly completed, even by a layman. The computation of the coefficients is practically automatic and greatly reduces the possibility of error.